(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tabugo SR, Claver PSS. 2022. Fractal analysis of seahorses in Mindanao, Philippines: A tale of their own. Biodiversitas 23: 5233-5238. Monitoring populations of species is essential for science-driven policymaking. However, monitoring can be a daunting task for threatened and vulnerable species like seahorses. They are often threatened by overfishing and habitat destruction in the marine environment. Since they are considered a flagship species, monitoring populations in Panguil and Murcielagos Bay, which served as the home of the two common seahorses in Mindanao, Philippines, is vital. Fractals naturally occur in nature and hence can be used as possible predictors. Morphometric complexity patterns were investigated in the Hippocampus kuda and Hippocampus comes via fractal geometry to delineate irregular non-euclidean objects. The difference between fractal dimension and lacunarity values was tested between species. The hypothesis states that high fractal dimensions are deviations from the equilibrium state/chaos and, thereby, can be linked to vulnerability. High mean fractal dimension (Da) based on box-counting and coefficient of variation (CV) of the lacunarity method were found in H. kuda (F) and H. comes (F). The observed variations can be attributed to morphological complexity as they have adapted to varied microhabitats. Herewith, fractals can be a fast, easy, convenient, and non-invasive way of monitoring species. The results of the study can support conservation protection measures for the two species.